The Lymphoma-Associated Macrophage to Hodgkin-Reed-Sternberg Cell Ratio Is a Poor Prognostic Factor in Classic Hodgkin Lymphoma Patients - Procházka, Vít; Papajík, Tomáš; Dýšková, Tereza; Dihel, Martin; Brychtová, Světlana; Prouzová, Zuzana; Kriegová, Eva; Lukášová, Marie; Hanáčková, Veronika (Clinical lymphoma, myeloma & leukemia, 2019)
BACKGROUND: Despite the relatively high rate of curability, approximately 20% to 30% of patients with classic Hodgkin lymphoma relapse. Hodgkin-Reed-Sternberg (HRS) cells:lymphoma-associated macrophages (LAMs) cross talk promotes tumor growth and resistance to therapy. The aim of the study was to assess the prognostic role of the LAM to HRS ratio (LHR) in lymph node biopsies using a novel automated system for scanning large sample areas. PATIENTS AND METHODS: High-quality tissue samples obtained from 71 patients and stained with anti-CD30 and anti-CD68 were analyzed using the TissueFAXS (TissueGnostics). RESULTS: A high LHR was associated with inferior 5-year progression-free survival (PFS; 50.0% vs. 79.3%; P = .032) and overall survival (OS; 65.4% vs. 92.3%; P = .012). Multivariate Cox regression identified the high LHR as an unfavorable prognostic factor for PFS (hazard ratio [HR], 3.07; P = .029) and OS (HR, 4.56; P = .025). CONCLUSION: A high LHR at diagnosis is associated with a higher risk of lymphoma progression or death. Automated image analysis is a new tool that can overcome technical limitations of by microarray samples in lymphomas with high intratumor heterogeneity.
Keywords: Young Adult; lymfatické uzliny; antigeny diferenciační myelomonocytární; antigen Ki-1; Disease-Free Survival; Male; buňky Reedové-Sternberga; lokální recidiva nádoru; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; Lymph Nodes; Reed-Sternberg Cells; Adolescent; prognóza; Antigens, CD; CD antigeny; Adult; biopsie; Aged; dospělí; mužské pohlaví; senioři; mladiství; Hodgkin Disease; Neoplasm Recurrence, Local; senioři nad 80 let; lidé; ženské pohlaví; Ki-1 Antigen; Humans; makrofágy; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; Hodgkinova nemoc; Prognosis; Biopsy; Female; Macrophages; lidé středního věku; přežití bez známek nemoci; Middle Aged; Antigens, Differentiation, Myelomonocytic